Comparison of the Effectiveness of Training based on Positive Psychology and Motivational Interviewing on Emotional Distress in Patients with Type 2 Diabetes - Hosseini Tavan, Seyed Hamid; Taher, Mahboobe; Nouhi, Shahnaz; Rajab, Assadollah (International Journal of Applied Behavioral Sciences, 2020)
Introduction: Prevalence of diabetes has been rising in Iran that causes many social and economic problems. The aim of this study was to compare the effectiveness of training based on positive psychology and motivational interviewing on emotional distress in patients with type 2 diabetes. Method: Quasi-experimental research design with pretest-posttest and control group were utilized in this study. The statistical population included patients with type 2 diabetes referring to the Endocrinology and Metabolism Research Institute. 48 patients were selected with convenient sampling method and divided into two experimental group and a control group. The first group received positive psychology training. The second group received a motivational interviewing and the control group did not receive any treatment. The groups were evaluated before and after the intervention using emotional distress questionnaire. Data were analyzed by using multivariate analysis of covariance. Result: The result showed positive psychology training and motivational interview training are effective on decreasing components of psychological distress including psychological distress in relation to diabetes management and depression-related problems in patients with diabetes and positive psychological training was more effective (p<0.05). Conclusion: Based on results of this study, positive psychological and motivational interviewing training have positive effect on emotional distress of type 2 diabetes patients. Both of the interventions by strengthening positive motivation and modifying the levels of negative effects reduced emotional distress scores.